Peran Pendidikan dalam Tantangan Era Revolusi Industri 4.0 menuju Era Revolusi Industri 5.0 - Bidari Andaru Widhi; Dyah Susilowati; Anthony Anggrawan; Helna Wardhana; Christofer Satria; Titik Ceriyani Miswaty (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The objectives of this activity are: to provide an understanding of the assumptive of education in facing the era of the industrial revolution 4.0 towards the era of the industrial revolution 5.0 for children in an effort to prevent early marriage and to build parental commitment to guide and monitor the use of gadgets for children in Dusun Salut Kendal, Desa Salut, Kecamatan Kayangan, North Lombok. This socialization activity is a collaboration between the Mataram Non-Governmental Organization (NGO) Selaksa Sejahtera Foundation (YASERA) and Bumigora University. The target of this devotion of people is around the Dusun Salut Kendal amount 40 people out of the planned 70 people which will be carried out in a day. The method of implementing this service is socialization which is the form of a workshop. Methods of socialization delivery of presentation and discussion techniques. The results of the implementation of Community Service show that the level of understanding of participants is more aware of the use of gadgets and the internet in facing the 4.0 industrial revolution era towards the 5.0 industrial revolution era for children in an effort to prevent early marriage.